How can metacognition be developed through problem-solving in higher education? (2011)
Teacher-guided academic activities undertaken by students emphasise the cognitive strategies and procedures necessary for their successful resolution when problem-solving in electronic engineering’s digital communications area. However, students do not approach knowledge regarding their learning abilities (metacognition) in such a way that self-knowledge, skills development assessment and controlling their own abilities and limitations are favoured when guiding their learning. This article presents some meta-cognitive features which have been identified in students regarding problem-solving strategies in teaching, learning and evaluating engineering.